Downregulation of cathepsin C alleviates endothelial cell dysfunction by suppressing p38 MAPK/NF-κB pathway in preeclampsia. Issue 2 (1st February 2022) - Lu, Fan; Gong, Han; Lei, Houkang; Li, Juan
ABSTRACT: Endothelial cell dysfunction is an essential pathophysiological feature of preeclampsia (PE). It has been reported that cathepsin C is upregulated in the maternal vascular endothelium of PE patients. The excessive activation of p38 MAPK leads to various diseases, including PE. NF-κB pathway can promote uteroplacental dysfunction, endothelial stress and development of PE. Moreover, it has been verified that cathepsin C can activate p38 MAPK/NF-κB pathway. In the present work, hypoxia/reoxygenation (H/R) injury model of HUVECs was established to discuss the biological functions of cathepsin C in endothelial cell dysfunction and to elucidate the underlying molecular mechanism. The correlation between cathepsin C and p38 MAPK/NF-κB pathway in H/R-stimulated HUVECs as well as the effects of cathepsin C and p38 MAPK/NF-κB pathway on viability, apoptosis, invasion, in vitro angiogenesis of HUVECs and oxidative stress were assessed. The results revealed that H/R injury elevated cathepsin C expression and activated p38 MAPK/NF-κB pathway in HUVECs and cathepsin C knockdown inhibited the activity of p38 MAPK/NF-κB pathway in H/R-stimulated HUVECs. Downregulation of cathepsin C improved viability, inhibited apoptosis and enhanced invasion of H/R-stimulated HUVECs. In addition, downregulation of cathepsin C alleviated oxidative stress and induced stronger HUVEC angiogenesis in vitro. Furthermore, the protective effects of cathepsin C knockdown against endothelial cell dysfunction were reversed by p38 MAPK activator anisomycin. In other words, downregulation of cathepsin C could improve HUVEC viability and enhance anti-apoptotic capacity, anti-oxidative capability, invasive ability, as well as angiogenic potential of H/R-stimulated HUVECs by repressing p38 MAPK/NF-κB pathway.